ANALISIS LAJU INFILTRASI TERHADAP CURAH HUJAN DAERAH GUNUNG PANCAR, BOGOR, JAWA BARAT : ANALYSIS OF INFILTRATION RATE OF RAINFALL IN MOUNT PANCAR, BOGOR, WEST JAVA - Syahra Kamila Khairani; Mohammad Apriniyadi; Muhammad Adimas Amri (Journal of Geoscience Engineering & Energy (JOGEE), 2022)
Infiltration rate and rainfall are one of the parameters in determining water catchment areas. In an area that has a high level of rainfall, it is very good to be a water catchment area. Water catchment areas must be maintained and protected so that they can be used to incrase groundwater reserves and prevent flooding, so a spatial plan is needed in determining water catchment areas. This study aims to determine the rate of infiltration in the ara of Mount Pancar, Bogor, West Java. Infiltration rate data was collected directly in the field using a double ring infiltrometer and rainfall data was obtained from BMKG data at Citeko Station. The final result of these data will be made a map of the infiltration rate and rainfall map. The results of the study in the study area obtained an infiltration rate of 0,096 m/day – 0,553 m/day with rainfaal of more than 3000 mm/year. From these data, it can be concluded that the rate og infiltration and rainfall are closely related to each other in determining water catchment areas.